Cell scientist to watch – Anjali Kusumbe - Anjali, K (The Company of Biologists, 2023)
Anjali Kusumbe is the head of the Tissue and Tumour Microenvironments Group at the MRC Human Immunology Unit and MRC Weatherall Institute of Molecular Medicine and Director of the Oxford Tissue Imaging Centre, UK. She completed her PhD with a fellowship from the Council of Scientific and Industrial Research in India, before moving to the Max Planck Institute for Molecular Biomedicine in Germany for her postdoc, where she worked on endothelial heterogeneity in bone. She established her group in Oxford in 2017 and was awarded the 2023 BSCB Women in Cell Biology Early Career Medal, and more recently the ISRB 2023 Rising Star Award. We caught up with Anjali over Zoom to ask about the BSCB award, her career path and her advice for new group leaders.